A behavioral and brain imaging dataset with focus on emotion regulation of women with fibromyalgia - Thania Balducci; Jalil Rasgado-Toledo; Alely Valencia; Marie-José van Tol; André Aleman; Eduardo A. Garza-Villarreal (Scientific Data, 2022)
Measurement(s) Blood Oxygen Level-Dependent Functional MRI • brain • Emotion Technology Type(s) functional magnetic resonance imaging • Magnetic Resonance Imaging • Emotion regulation task Factor Type(s) valence • emotion regulation condition Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment laboratory environment Sample Characteristic - Location Mexico